2021
DOI: 10.3390/agronomy11112315
|View full text |Cite
|
Sign up to set email alerts
|

Kompetitive Allele Specific PCR (KASP) Markers for Potato: An Effective Tool for Increased Genetic Gains

Abstract: Potato virus Y (PVY) and Phytophthora infestans (Mont.) de Bary that causes potato late blight (LB), pose serious constraints to cultivated potatoes due to significant yield reduction, and phenotyping for resistance remains challenging. Breeding operations for vegetatively propagated crops can lead to genotype mislabeling that, in turn, reduces genetic gains. Low-density and low-cost molecular marker assessment for phenotype prediction and quality control is a viable option for breeding programs. Here, we repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 56 publications
(62 reference statements)
0
12
0
Order By: Relevance
“…For screening many hundreds or thousands of individuals, the KASP genotyping service offered through the CGIAR Excellence in Breeding (EiB) initiative has been valuable for public breeding programs. The first potato KASP markers developed for the EiB service targeted variants linked to Ry adg (Herrera et al 2018; Kante et al 2021) and Ry sto (Nie et al 2016), which confer extreme resistance to potato virus Y. More recent targets include the late blight resistance genes R2/Rpi-abpt/Rpi-blb3 on chr04 (Meade et al 2020; Karki et al 2021) and R8/Rpi-smira2 on chr09 (Kante et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For screening many hundreds or thousands of individuals, the KASP genotyping service offered through the CGIAR Excellence in Breeding (EiB) initiative has been valuable for public breeding programs. The first potato KASP markers developed for the EiB service targeted variants linked to Ry adg (Herrera et al 2018; Kante et al 2021) and Ry sto (Nie et al 2016), which confer extreme resistance to potato virus Y. More recent targets include the late blight resistance genes R2/Rpi-abpt/Rpi-blb3 on chr04 (Meade et al 2020; Karki et al 2021) and R8/Rpi-smira2 on chr09 (Kante et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The first potato KASP markers developed for the EiB service targeted variants linked to Ry adg (Herrera et al 2018; Kante et al 2021) and Ry sto (Nie et al 2016), which confer extreme resistance to potato virus Y. More recent targets include the late blight resistance genes R2/Rpi-abpt/Rpi-blb3 on chr04 (Meade et al 2020; Karki et al 2021) and R8/Rpi-smira2 on chr09 (Kante et al 2021). According to Haverkort et al (2016), R8/Rpi-smira2 compares favorably to RB / Rpi-blb1 in terms of durability, while R2/Rpi-abpt/Rpi-blb3 only offers “intermediate” spectrum resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To validate the suitability of the set of SNPs, these were converted into a KASP assay, which is a uniplex SNP genotyping platform. Previous research has been reported on the generation of KASP markers in a variety of crop species, including rice, wheat, maize, bajra, sorghum, tomato, potato, cotton, peanut, and rubus species ( Rasheed et al, 2016 ; Zhao et al, 2017 ; Ryu et al, 2018 ; Steele et al, 2018 ; Burow et al, 2019 ; Devran and Kahveci, 2019 ; Chen et al, 2021 ; Kante et al, 2021 ). A total of six of our designed SNPs were able to distinguish the resistant and susceptible lines, which correlated with our previous phenotyping results ( Lakshmi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the HTPG has transitioned into an EIB platform, and the shared services are offered as EiB low-density genotyping service (EiB-LDSG) ( CGIAR, 2021 ). KASP-based genotyping was well used through the HTPG/EiB-LDSG with the successful development of markers for target traits along with the use of the existing KASP markers for introgression of target traits in a number of crops including groundnut ( Parmar et al, 2021 ), sorghum ( Mwamahonje et al, 2021 ), potato ( Kante et al, 2021 ; Sood et al, 2022 ), cassava ( Thuy et al, 2021 ), and rice ( Arbelaez et al, 2019 ). Among the marker panels of rice with the HTPG, few SNPs related to BPH resistance for genes Bph17 , Bph32 , and Bph9 are available ( Excellence in breeding, 2021 ) and can be genotyped for further use as diagnostic markers.…”
Section: Introductionmentioning
confidence: 99%